ANALISIS FAKTOR PARTISIPASI IBU HAMIL MELAKUKAN SKRINING HIV DI WILAYAH PUSKESMAS TUNTUNGAN KABUPATEN DELI SERDANG TAHUN 2021 - Mariasi Silalahi (Jurnal Penelitian Keperawatan Medik, 2022)
The hospital as a public institution that focuses on providing health services Transmission of HIV infection to children who are transmitted by the mother while in the womb or during childbirth will usually show signs within the first 12-18 months of a child's life. However, the participation of mothers participating in HIV screening during pregnancy is still low. The purpose of this study was to analyze the participation factors of pregnant women in HIV screening at Tuntungan Health Center. This research is an analytic survey research with cross sectional design. The research was conducted at the Tuntungan Public Health Center, Pancur Batu District. The study population was 842 people and a sample of 822 people. Data analysis used univariate analysis, bivariate analysis with chi-square, and multivariate analysis using multiple logistic regression tests at the 95% confidence level ( = 0.05). The results showed that the factors that influenced the participation of pregnant women in HIV screening at Tuntungan Public Health Center, Pancur Batu District were husband's support (p = 0.001), access to health services (p = 0.033), and needs (p = 0.001). Meanwhile, the factors that did not influence were age (p = 1,000), education (p = 1,000), and trust (p = 0.614). The most dominant factor influencing needs. The need variable has a value of Ratio Prevalence (RP) = 8.299, meaning that respondents who stated that HIV screening was a necessity had an 8.2 times higher chance of doing HIV screening than respondents who stated that HIV screening was not a necessity. It is recommended that the leaders of the Tuntungan Health Center promote health education through outreach to the community, especially pregnant women about HIV screening and HIV / AIDS disease to increase public knowledge (mothers and husbands) so that husbands can provide optimal support for mothers to carry out HIV screening during pregnancy.